Resistance to change: FGM/C and gendered inequality in Senegal - Falcão, R. (IV International Seminar MAP-FGM, 2018)
This paper is part of an ongoing research on Sexual and Reproductive Rights in West Africa, with a particular focus in Senegal. It starts with the assumption that the body is a signifier of local social and moral worlds, and also that it is through the body that experiences of freedom and autonomy, violence, social pressure and inequality are manifested. Individuals are socially situated through their gender but gender representations are disputed by social actors, endogenous and exogenous. The claims for social change concerning FGM/C envisions an abandonment of the practice as part of a social project that isn’t always shared with practicing communities in the same lines as those set by stakeholders. Political and activist mobilisation often fails to anticipate backlashes. With this paper I want to claim that we have to cast a wider view on gender inequality, social values and norms, because both practicing and non-practicing communities share cultural representations that fuel an overepresentation of femininity, female sexuality and the female body and its link to social order and morality.